MENGEMBANGKAN KETERAMPILAN PROSES SAINS SISWA SEKOLAH DASAR MELALUI MODEL INKUIRI TERBIMBING - Sudarsri Lestari; Erisy Syawiril Ammah; Endhang Suhilmiyati (AT TA'LIM : Jurnal Madrasah Ibtidaiyah, 2023)
This study aims to (1) find out how the application of guided inquiry models to learning in elementary schools, (2) find out whether there are differences in students' science process skills before and after learning through guided inquiry models, and (3) knowing how the development of students' science process skills through guided inquiry models. This type of research uses mixed methods embedded experimental design, using interviews, observations, questionnaires, and tests as data collection methods. The research subjects consisted of 24 elementary school students. The results of the study show that: (1) the application of a guided inquiry model is carried out by the stages of expressing problems, preparing experiments or investigations, conducting experiments or investigations in groups, compiling reports on the results of experiments or investigations, and presenting the results; (2) there are differences in students' science process skills before and after learning through guided inquiry models; (3) students' science process skills through guided inquiry models experience fluctuating developments.